Synthesis and Antifungal Activity of N1-Nicotinoyl-3-Methyl-4-(substituted Azo)-1,2-Pyrazoline-5-One - Nayal, S.S.; Singh, C.P. (Asian Journal of Chemistry, 2010)
A novel series of N1-nicotionyl-3-methyl-4-(sulpha/substituted phynyl azo)-1,2-pyrazoline-5-one have been synthesized by the condensation of sulpha/substituted phenyl azo ethyl-3-oxobutyrate with nicotinic acid hydrazide, using glacial acetic as condensing agent. Some of the products showed significant antifungal activity agianst C. albicans, C. neoformans, S. schenikkii, T. mentagrophytes and A. fumigatus.